Accelerating section for technological electron linac - Ayzatsky, M.I.; Biller, E.Z.; Dovbnya, A.N.; Kramarenko, K.Yu.; Khodak, І.V.; Kushnir, V.A.; Mytrochenko, V.V.; Nikitina, T.Ph.; Opanasenko, A.M.; Perezhogin, S.A.; Stepin, D.L.; Selivanov, L.I.; et al. (Вопросы атомной науки и техники, 2016)
The construction parameters and electrodynamic characteristics of the accelerating section with phase advance of 120° at the operating frequency of 2856 MHz are presented. This section is designed to upgrade the electron LINAC LU-10 at NSC KIPT. Experimental results are compared with calculated ones.